"… They don't really listen to people": Young people's concerns and recommendations for improving online experiences. Issue 2 (13th May 2019) - Creswick, Helen; Dowthwaite, Liz; Koene, Ansgar; Perez Vallejos, Elvira; Portillo, Virginia; Cano, Monica; Woodard, Christopher
Abstract : Purpose: The voices of children and young people have been largely neglected in discussions of the extent to which the internet takes into account their needs and concerns. This paper aims to highlight young people's lived experiences of being online. Design/methodology/approach: Results are drawn from the UnBias project's youth led discussions, "Youth Juries" with young people predominantly aged between 13 and 17 years. Findings: Whilst the young people are able to use their agency online in some circumstances, many often experience feelings of disempowerment and resignation, particularly in relation to the terms and conditions and user agreements that are ubiquitous to digital technologies, social media platforms and other websites. Practical implications: Although changes are afoot as part of the General Data Protection Regulation (herein the GDPR) to simplify the terms and conditions of online platforms (European Union, 2016), it offers little practical guidance on how it should be implemented to children. The voices and opinions of children and young people are put forward as suggestions for how the "clear communication to data subjects" required by Article 12 of the GDPR in particular should be implemented, for example, recommendations about how terms and conditions can be made more accessible. Originality/value: Children and young people are an often overlooked demographic of online users. This paper argues for the importance of this group being involved in any changes that may affect them, by putting forward recommendations from the children and young people themselves.